Problematic aspects of the appeal against the resolution by which a question of the acceptance of a statement of claim is resolved - Biveinytė, Roberta; Dambrauskaitė, Aušrinė (Vilnius University Open Series, 2021)
This article is dedicated to analyse problematic aspects of the appeal against the resolution by which a question of the acceptance of a statement of claim is resolved; the article also presents analysis of the Lithuanian case law from 2013 to 2020 on this matter and its compliance with the regulation enshrined in the Code of civil procedure of the Republic of Lithuania.